Distribution and Impact of Parthenium (Parthenium hysterophorus L.) on Weed Species Diversity in Maize Fields in Western Gojjam Zone, Amhara National Regional State, Ethiopia. (10th April 2021) - Million, Dinberu; Nigatu, Lisanework; Bekeko, Zelalem; Legesse, Hirpa
Abstract : An investigative weed flora survey was conducted in parthenium-infested maize fields in West Gojjam Zone in 2019/2020. The objective was to investigate the distribution and impact of parthenium on species diversity. A survey was conducted on 90 fields using 2 m × 2 m (4 m 2 ) quadrats (totally 270). A total of 110 weed species belonging to 27 families were identified out of these families. Asteraceae with 26 species (23.36%) and Poaceae with 18 species (16.36%) were abundant. The highest importance value (IV) was recorded by Ageratum conyzoides, Amaranthus hybridus, and Bidens pilosa, with 28.05, 19.18, and 13.16%, respectively, in no parthenium infestation level. The highest IV of 27.08, 17.71, and 16.44%, respectively, was shown by Ageratum conyzoides, Bidens pilosa, and Galinsoga parviflora with 27.08, 17.71, and 16.44%, respectively, in very low parthenium infestation level. Ageratum conyzoides (29.38%), Bidens pilosa (24.10%), and Parthenium hysterophorus (22.68%) had the highest IV in low parthenium infestation level. Parthenium hysterophorus (91.32%), Ageratum conyzoides (17.19%), and Echinochloa colona (16.34%) had high IV in moderate parthenium infestation level. It is concluded that Ageratum conyzoides, Bidens pilosa, Echinochloa colona, and Galinsoga parviflora were competitive over parthenium based on importance value, and this indicates to suggest parthenium as a biological management option.